(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
While there are many studies conducted on software risk during the last two decades, very few have been published on software risk management practice in IT industry. In this paper we explore industry practice in the management of software development risks in outsourced software migration projects. We take the vendor perspective, post contract finalization. We conducted an online survey of 145 software projects executed by global IT vendors with process maturity of CMM Level 5. Based on this we built a statistical model relating software risk management factors with project outcome. An embedded case study of a large software migration project executed for a fortune 500 company was undertaken to check whether the model agrees with actual industry practice. The best practices and experiences from the project are also shared.